Hemangioma of uterine cervix associated with high-grade squamous intraepithelial lesion - Djolai, Matilda; Bošković, Tamara; Djurdjevic, Srdjan; Trivunić Dajko, Sandra; Andrejić Višnjić, Bojana; Rajović, Ranko (Vojnosanitetski pregled, 2015)
Introduction. Benign, especially polypoid, lesions of the cervix are common in everyday work.  Rare tumors of this region are vascular ones, particularly capillary and/or cavernous hemangiomas. Cervical hemangiomas are especially rare, usually asymptomatic and only one third of the cases is clinically manifested as vaginal bleeding, polyps, etc. Case report. We reported a 54-year-old postmenopausal female patient who had undergone conization due to high-grade squamous intraepithelial lesion (H-SIL). Microscopic analysis of slices confirmed the existence of dysplastic changes in the endocervical epithelium and in small part in the epithelium of the gland of H-SIL type. In 2 of 15 slices, within the walls of the cervix, dilated, amplified and abnormal blood vessels lined with endothelium were observed, vaguely limited by the surrounding connective tissue of lamina propria and smooth muscle wall of the cervix. According to the pathological characteristics, the change corresponded to the hemangioma. Both changes were completely removed. Conclusion. In comparison with the available literature data, the presented case is the first to describe the association of hemangioma and dysplastic changes in the endocervical epithelium. Hemangioma was incidentally discovered in the histological sections of the material after the conization in a postmenopausal women.
Keywords: cervix uteri; hemangioma; uterine cervical dysplasia; comorbidity